Inhibitory effect of luteolin on the metabolism of vandetanib in vivo and in vitro - Shen, Yuxin; Hong, Fengsheng; Wu, Hualu; Chen, Xiaohai; Xia, Hailun; Xu, Ren-ai; Lin, Guanyang; Shi, Lu (Frontiers in Pharmacology, 2025)
This study aimed to examine the potential drug-drug interaction (DDI) between vandetanib and luteolin in vivo and in vitro, with the objective of establishing a scientific foundation for their appropriate utilization in clinical settings. Sprague-Dawley (SD) rats were randomly divided into two groups: a control group (vandetanib administered by gavage alone) and an experimental group (vandetanib and luteolin administered together). A series of blood samples were collected at different time intervals. The plasma concentrations of vandetanib and its metabolite N-demethyl vandetanib in rats were determined using an ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). Incubation systems were set up with rat liver microsomes (RLM) and human liver microsomes (HLM) to measure the Michaelis-Menten constant (Km) and half-maximum inhibitory concentration (IC50) values. Additionally, the inhibitory mechanism of luteolin on vandetanib was also investigated. Ultimately, the molecular mechanism of inhibition was examined through the utilization of molecular docking techniques. In vivo animal experiment results showed that compared with the control group, the AUC(0-t) and Cmax of vandetanib in the experimental group were significantly increased. The findings from the in vitro experiments revealed that luteolin exhibited a moderate inhibitory effect on the metabolism of vandetanib. The IC50 values for RLM and HLM were determined to be 8.56 μM and 15.84 μM, respectively. The identified inhibition mechanism was classified as mixed. This study utilized molecular docking analysis to provide additional evidence supporting the competitive inhibition of luteolin on vandetanib in CYP3A4. The data presented in our study indicated a potential interaction between vandetanib and luteolin, which may necessitate the need for dose adjustment during their co-administration in clinical settings.